Roads and Road-Posts as an Ecological Trap for Cavity Nesting Desert Birds - Ben-Aharon, Nimrod; Kapota, Dror; Saltz, David (Frontiers in Conservation Science, 2020)
We investigated whether roads in a desert environment in southern Israel act as an ecological trap for the territorial mourning wheatear (Oenanthe lugens). We applied an individual-based mechanistic approach to compare the apparent survival of individually-marked wheatears between roadside territories and territories in natural habitats further away from the road, and determined directionality in territorial shifting to and from the road. Analysis was based on mark-resight techniques and multi-model inference in a multi-strata approach (program MARK). Wheatear survival in road-side territories was too low to be compensated by the maximum possible recruitment, but shifted territories from natural habitat towards the roadside habitat as these territories were vacated by mortality. Vacated territories along the road were re-occupied faster than vacated territories in natural habitat. Thus the roadside habitat in our study area fulfilled all conditions for an ecological trap. Roads may act as widespread ecological traps and their impact, therefore, may extend well beyond the existing perception of narrow dissecting elements causing local mortality and/or animal avoidance. In species where habitat selection is based on contest competition (e.g. territorial species) and contest success has a genetically heritable component, ecological traps will induce a paradoxical selection process.